The effects of protectionism on a small country the case of Uruguay (World Bank regional and sectoral studies, 1994)
"Competently executed series of studies on the distorted trade regime of Uruguay until the late 1980s and the effect of protectionism on a variety of economic outcomes. Topics covered range from the political economy of trade distortions to the sectoral impact of specific regulations. Worth reading"--Handbook of Latin American Studies, v. 57